A decade of regional geochemistry in China: the National Reconnaissance Project - Xuejing Xie; Tianxiang Ren (The Institute of Materials, Minerals and Mining, 1991)
Paper presented at the 28th International Geological Congress held in Washington DC, July 1989 (International geochemical mapping sessions). Standardised stream-sediment sampling procedures have been used in mountainous and hilly terrains. Special sampling procedures were developed for application in remote environments, such as high mountains, desert, semi-desert, karst and loess-covered regions. The diversified analytical methods used in more than 20 analytical laboratories participating in the project have been unified into two multi-element, multi-method analytical systems. A unified data monitoring procedure was developed based on primary and secondary standard samples. To date the project has covered about 4 000 000 km2 and the aim is to complete the coverage within the present decade